The effects of split injections on high exhaust gas recirculation low-temperature diesel engine combustion. (February 2013) - Sarangi, Asish K; Garner, Colin P; McTaggart-Cowan, Gordon P; Davy, Martin H; Wahab, Emad; Peckham, Mark
Diesel engine emissions of oxides of nitrogen and smoke can be reduced simultaneously through the use of high levels of exhaust gas recirculation to achieve low-temperature combustion. However, single fuel injection per cycle diesel low-temperature combustion is also characterized by high fuel consumption and high total unburned hydrocarbons and carbon monoxide emissions. This work focuses on investigating the potential of a split (50/50) main fuel-injection strategy to reduce smoke, total unburned hydrocarbons and carbon monoxide emissions at exhaust gas recirculation levels lower than those required to achieve single-injection diesel low-temperature combustion at a medium-load, medium-speed operating condition. Experiments were performed on a 0.51 l single-cylinder high-speed direct-injection diesel engine running at 1500 r/min at an operating condition corresponding to a gross indicated mean effective pressure of 500 kPa. At this load, exhaust gas recirculation levels of 62% are needed to realize near-zero nitrogen oxide and smoke emissions, but this leads to an unacceptable reduction in thermal efficiency as well as high total unburned hydrocarbons and carbon monoxide emissions. This work compares the effects of split fuel injections at an exhaust gas recirculation level of 52% by volume to those from single injections at exhaust gas recirculation levels of 52% and 62%. The results demonstrate that the combined effects of exhaust gas recirculation rate and split injections can achieve near-zero nitrogen oxide with good thermal efficiency and total unburned hydrocarbons and carbon monoxide emissions much lower than at 62% exhaust gas recirculation. Single injection at this point results in excessive smoke, which can be reduced by over 75% through the split-injection strategy. These results are particularly relevant as they demonstrate very low nitrogen oxide emissions from an engine operation with acceptable thermal efficiency and at practical exhaust gas recirculation levels.